Successful application of ancient DNA extraction and library construction protocols to museum wet collection specimens. (16th June 2021) - Straube, Nicolas; Lyra, Mariana L.; Paijmans, Johanna L. A.; Preick, Michaela; Basler, Nikolas; Penner, Johannes; Rödel, Mark‐Oliver; Westbury, Michael V.; Haddad, Célio F. B.; Barlow, Axel; Hofreiter, Michael
Abstract: Millions of scientific specimens are housed in museum collections, a large part of which are fluid preserved. The use of formaldehyde as fixative and subsequent storage in ethanol is especially common in ichthyology and herpetology. This type of preservation damages DNA and reduces the chance of successful retrieval of genetic data. We applied ancient DNA extraction and single stranded library construction protocols to a variety of vertebrate samples obtained from wet collections and of different ages. Our results show that almost all samples tested yielded endogenous DNA. Archival DNA extraction was successful across different tissue types as well as using small amounts of tissue. Conversion of archival DNA fragments into single‐stranded libraries resulted in usable data even for samples with initially undetectable DNA amounts. Subsequent target capture approaches for mitochondrial DNA using homemade baits on a subset of 30 samples resulted in almost complete mitochondrial genome sequences in several instances. Thus, application of ancient DNA methodology makes wet collection specimens, including type material as well as rare, old or extinct species, accessible for genetic and genomic analyses. Our results, accompanied by detailed step‐by‐step protocols, are a large step forward to open the DNA archive of museum wet collections for scientific studies.